ADSORPTION AND CORROSION INHIBITIVE PROPERTIES OF ORYZA GLABERRIMA HUSK EXTRACT ON ALUMINIUM IN H2SO4 SOLUTION: ISOTHERM, KINETIC AND THERMODYNAMIC STUDIES - POPOOLA, Lekan Taofeek (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In this study, isotherm, kinetic and thermodynamic studies of corrosion inhibitory properties of Oryza Glaberrima husk extract (OGHE) on aluminium in 1.5 M H2SO4 solution was investigated via mass loss measurement. Aluminium coupon and OGHE were characterized using SEM, EDS, FTIR and AAS. Increase in Al corrosion rate in H2SO4 solution was observed as exposure period (24 - 120 hrs) and temperature (293 - 333K) were increased but decreased with pH (2 - 6). Corrosion inhibition efficiency of OGHE is a function of its concentration and ability to be easily absorbed on Al surface to form thick protective films against H2SO4 attack. Adsorption of OGHE molecule on Al surface in 1.5 M H2SO4 solution agrees excellently well with Langmuir isotherm. Thermodynamic study revealed the adsorption process to be spontaneous, endothermic and physisorption in nature. Kinetic study affirmed adsorption of OGHE molecule on Al surface to obey second order reaction. Appropriate corrosion mechanisms of Al dissolution in H2SO4 and in the presence of OGHE were proposed. This study proved positive prospects of OGHE as effective corrosion inhibitor for Al in acidic medium.